2020
DOI: 10.1371/journal.pone.0240844
|View full text |Cite
|
Sign up to set email alerts
|

Cruciform DNA in mouse growing oocytes: Its dynamics and its relationship with DNA transcription

Abstract: Cruciform DNA is a causing factor of genome instability and chromosomal translocation, however, most studies about cruciform DNA in mammalian cells were based on palindromic sequences containing plasmids and reports about endogenous cruciform DNA are rare. In this study we observed the dynamics of endogenous cruciform DNA in mouse growing oocytes using immunofluorescence labeling method. We found cruciform DNA foci exist in transcription active growing oocytes but not in transcription inactive fully grown oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Moreover, using the immunofluorescence labeling method and 2D3 cruciform binding antibody, Feng et al [ 112 ] demonstrated the presence of cruciforms in mice growing oocytes. Interestingly, cruciform foci were detected in different phases of oocyte growth but were no longer present in fully grown oocytes (characterized by silencing of transcription activities, chromatin condensation and formation of a Hoechst-positive ring-like structure surrounding the nucleolus).…”
Section: Dna Palindromes In the Human Genomementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, using the immunofluorescence labeling method and 2D3 cruciform binding antibody, Feng et al [ 112 ] demonstrated the presence of cruciforms in mice growing oocytes. Interestingly, cruciform foci were detected in different phases of oocyte growth but were no longer present in fully grown oocytes (characterized by silencing of transcription activities, chromatin condensation and formation of a Hoechst-positive ring-like structure surrounding the nucleolus).…”
Section: Dna Palindromes In the Human Genomementioning
confidence: 99%
“…Cruciform foci colocalized with PARP1 (poly(ADP-ribose)-polymerase, a protein involved in DNA damage sensing (mainly of single-stranded breaks), which was previously shown to bind hairpin loops [ 113 ], but not with γH2A.X, indicating that in normal oocytes, a cruciform-induced DSB is probably rare. Additionally, Feng et al [ 112 ] analyzed data from The Genotype-Tissue Expression Project (GTEx, [ 114 ]) to see the expression pattern for PATRR11- and PATRR22-related transcripts in various human tissues. They found that the nearest transcript to PATRR11 (located about 1 kb downstream of PATRR11) is specifically expressed in liver and testes and that PATRR22 is located in the intron of a gene also specifically expressed in testes.…”
Section: Dna Palindromes In the Human Genomementioning
confidence: 99%
“…There is a growing number of bioinformatic tools for UNas prediction and biophysical characterization [45,[56][57][58][59] as well as for determining their roles in various diseases including cancer [60,61]. Contemporary, specific antibodies against cruciforms [62,63], lefthanded nucleic acids [64], G-quadruplexes [65], and i-motifs [66] have also been developed, allowing effective analyses of UNas both in vitro and in situ. Even if UNas are often difficult to sequence, current methods and their modifications [67] allow accurate sequencing and determination in genomes, leading to the finalization of telomere-to-telomere gapless assemblies [68][69][70][71].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Inverted repeats located in the promoter regions of genes are preferentially bound by many transcription factors ( Table 1 ), such as PARP-1, BRCA1, ER, and p53 [ 15 , 70 , 90 ]. The tumour suppressor protein p53 is critical for protection against many human cancers.…”
Section: A Range Of Proteins Interact With Cruciformsmentioning
confidence: 99%
“…It has also been demonstrated that cruciforms in gene promoters impact transcription upon oxidative modification of 2’-Deoxyguanosine [ 123 ]. The association of cruciforms with the regulation of transcription [ 90 ], as discussed above, opens other therapeutic windows where the specific levels of gene expression are influenced by the their presence and stability in promoter regions. An important tool allowing such approaches is the monoclonal antibody with specificity to the cruciform structure, although up to now, this has only been used for research purposes [ 28 , 69 , 124 ].…”
Section: Inverted Repeats and Cruciforms As Potential Therapeutics In...mentioning
confidence: 99%